The nature of the cavernous hemangioma and comparison Mr image and Ki-67 proliferating index - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2008)
The pathogenesis of cerebrovascular malformations is currently unknown. Lately recent researchs suggest that their pathogenesis and development might be due to various factors taking part in the angiogenesis. Cavernous hemangiomas (CHs) are considered as dynamic lesions. Until now, in the relevant literature only four studies about anti-Ki-67 proliferating index (MIB-1) of CHs have been cited. The mainstay of this study is definition of Ki-67 reactivity in CHs. Ten paraffin embedded sections stained immunohistochemically with antibodies to Ki-67 were analyzed. In this study MRI of the 10 CH's were grouped according to the Zabramski's classifications. According to Zabramski's classification distribution of our cases were type I 4 cases, type II 3 cases and type III 3 cases. Labeling index for Ki-67 were found to be immunopositively reacting in endothelial cells of 4 cases of CHs (40%) (2 type I; 1 type II, 1 type III). The relation between MRI and Ki-67 proliferative index were similar and there was no relation between the types of CHs regarding with MRI classification of Zabramski.
Keywords: cerebrovascular malformations; cavernous hemangioma; Ki-67; immunohistochemistry; ARTERIOVENOUS-MALFORMATIONS; EXPRESSION; HISTORY